A First Report: Two Cases of Survival and Full Recovery After Blunt Cardiac Rupture Requiring Emergency Department Thoracotomy. Issue 5 (May 2020) - Weber, Courtney; Farrah, Jason; Garcia, Alejandro; Ang, Darwin
Blunt traumatic cardiac rupture is an uncommon event in trauma and survival is rare. While multiple isolated accounts of repair of blunt cardiac rupture have been reported in the literature, there is not a single report of survival from right ventricular rupture following an emergency department thoracotomy (EDT). We report 2 cases where patients have survived such injuries and have made a full recovery. These patients are from a single institution who lost pulses on arrival to the emergency department; then underwent EDT with relief of cardiac tamponade with hemorrhage control by temporary closure, and subsequent definitive repair of right ventricular rupture in the operating room. Both were multiply injured and survived to discharge without neurologic sequelae and have made a full recovery back to their baseline function. This setting may represent an important use of EDT among blunt trauma patients, where time to survival and recovery may dependent on the speed of hemorrhage control and return of cardiac activity.